SED i jej stanowisko wobec Praskiej Wiosny 1968 i kryzysu w Polsce 1980–1981 - Kubina, Michael (Pamięć i Sprawiedliwość, 2007)
SED [The Socialist Unity Party of Germany, Sozialistische Einheitspartei Deutschlands] accurately valued the situation in the case of both crisises, in Prague in 1968 and in Poland in the end of 1980 and the beginning of 1981, correctly judging the critical infl uence of triumph of communist reforms in Prague a “Solidarność” in Poland on its own interest. It was obvious, that the case was the power, and the bolsheviks had no doubts that if the case was the power there is no place for any compromise. Their diagnosis was thus correct. In 1968 and in the beginning of 1981 one could still think about the radical therapy. The system had to be cleaned from the germs, from any kind of seeking for reforms. The immune system had to be strenghtened, that is the marxism-leninism study. Although the diagnosis was correct, the therapy did not bring effects. The disease turned to be incurable, the immune system was becomming weaker and weaker with every illness, and the virus, the individual pursuit for freedom, for shaping one’s own life oneself, could not be fought with. SED accurately judged the danger: what happened in Prague could not be reconciled with the system, it was undermining its basis and had to lead to collapse of the bolsheviks’ regime.In the end of 1980 and the beginning of 1981 Prague was a point of reference for SED. The only thing to do was to analyse the situation in Poland, compare it to what had happened in Prague in 1968 to understand, how big was a risk of a danger. As soon as mid August the SED leaders were convinced that events inPoland are a great challenge for the whole socialist block, and for the SED itself. Two weeks later, after the August agreement between the government and the Inter-Enterprise Strike Committee it became clear for SED that this was a counterrevolution. When evaluating the dangers which resulted from the events in Prague in 1968 and in Poland in 1980 and 1981 for the power and unity of the Soviet imperium, SED was very real. Policy of Ulbricht and Honecker towards Moscow was not awkward at all, they were trying to gain as much as possible for SED in the generally unfavourable conditions.However, this is the knowledge that we have gained only recently. Moreover the Honecker policy – irrespective of its inner inconsistencies – fell not in Bonn but in Moscow. Honecker did not foresee the Gorbachov arrival. However, he was not lonely in this neither on the West, nor in the East.